A modularised typology for flow design based on decoupling points – a holistic view on process industries and discrete manufacturing industries. Issue 16 (9th December 2016) - Wikner, Joakim; Noroozi, Sayeh
Abstract: Management of production activities covers a wide range of decisions. In this paper, a modularised approach is suggested that, through configuration, generates a case-specific flow design. The approach is based on identification of decision categories that are generic and fundamental in the flow design, covering both discrete manufacturing industries and process industries. Each decision category identifies a unique property of the flow which changes at a particular point: this is termed a 'decoupling point'. A three-dimensional modularised typology is developed by combining three different decision categories. Cases from the steel industry and the tooling industry are used to illustrate how the typology can be applied. The modularised approach provides a typology for the application of both qualitative and quantitative methods for flow management, including planning, control and performance management.